Analysis of constraints and innovation of chemistry experiment implementation in high school in Deli Serdang, Indonesia - Fathia Namira; Wan Azura; Ayu Miranda; Hamidatun Nisa; Saronom Silaban; Retno Dwi Suyanti; Ayi Darmana (Jurnal Pendidikan Kimia (JPKim), 2020)
Practical activities play an important role in science education. Through it, students develop a deeper understanding of standing theoretical concepts, skill, utilization of technology, and methods for investigation with direct manipulation of related materials. Effective use of laboratories is one of the requirements in learning chemistry, especially in experiment material. However, problems that are often encountered in learning in the laboratory are laboratory management which includes the procurement process, application process, and the maintenance process. The research method used was observation, document recording and interview with all chemistry teachers and students at Labuhan Deli Senior High School and Percut Sei Tuan Senior High School, District of Deli Serdang, Indonesia. Stages in the research of this are (1) observation based on National Education Standards, (2) observation of chemistry experiments implementation, (3) observation of constraint and problems laboratory at school, and (4) determine alternative solution. The result showed that area of chemistry laboratory has suitable with BSNP standart, but the standard of facilities and infrastructure category reference scale (PAP), showed less category results. So the settlement by researchers on this problem is to do a simple practicum that can be done in an open space or using the technology (virtual laboratory) to increase the students’ skill in industrial 4.0.Keywords: Chemistry experiment, Laboratory, Facilities, Simple practicum, Technology